Structural interpretation using seismic attributes: a case study from the offshore Orange Basin, South Africa - Donga, Buhle (My University, 2019)
The Orange Basin is located offshore, west coast of South Africa. The basin is known for its proven main hydrocarbon reserves and potential for further discoveries. Previous studies suggest that the basin is characterized by several gas chimneys; which can create pathways for gas migration from the source rock to the surface. It therefore is of critical importance to map and understand these structural features in the Orange Basin. In this study, highresolution, post-stack migrated 3D reflection seismic data, covering an area of ~ 308 km2, have been interpreted using conventional methods and state-of-the-art seismic attributes. The main objectives are to illuminate the large scale and sub-seismic geological structures that crosscut the hydrocarbon source rocks and act as conduits for gas migration to the surface. Horizon- and volume-based seismic attributes have been applied to improve visualization of structural relationships and to enhance the detection of Direct Hydrocarbon Indicators (DHIs). Seismic attributes are also used to map the relationship between structures, thus constraining their timing of activity. The results suggest that the study is characterised by NW-SE trending major normal faults, NW-SE and NE-SW trending subtle normal faults. Some of these faults fall below the seismic resolution limit (a quarter of the dominant wavelength) and cannot be mapped using conventional seismic interpretation techniques. However, their detection was enhanced through the use of seismic attributes. The complex trace attributes identify the general locations of major faults; the dip attribute provides the orientations of major faults in the study area; the dip-azimuth, edge detection and ant-tracking attributes examine the connectivity between major faults and linear faults mapped as minor fault segments which is not otherwise clear on conventional seismic amplitude data; the variance and ant-tracking attributes have mapped the major faults. The edge detection attributes also reveal the presence of pockmarks and gas chimneys characterized by low-amplitude reflections. This study is one of the first attempts to study the structural setting, timing of fault activity and the tectonic history of the offshore Orange Basin through the interpretation of high resolution 3D seismic data. This study proposes that the state-of-the-art seismic attributes should be recognised as fundamental seismic interpretation tools in studying the tectonic history of the region and to map structures that have major controls on hydrocarbon migration and storage.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science to the School of Geosciences, University of the Witwatersrand, Johannesburg, 2019
Keywords: Natural gas--Prospecting; Shale gas industry--Environmental aspects--South Africa